Effect of metallic reinforcement and mechanically mixed layer on the tribological characteristics of Al-Zn-Mg alloy matrix composites under T6 treatment. Issue 1 (31st December 2023) - Shetty, Raviraj J; Hindi, Jamaluddin; B M, Gurumurthy; Hegde, Ananda; Y M, Shivaprakash; Sharma, Sathyashankara; Murthy A, Amar; K, Muralishwara
Abstract: Owing to their high strength, high specific modulus, low co-efficient of thermal expansion, and excellent wear resistance, aluminium metal matrix composites reinforced with hard ceramic particles are employed in different domains. The primary heat treatment method employed to enhance the desirable properties of heat-treatable aluminium alloys and their composites is T6 treatment. This study investigated the effects of metallic reinforcement and mechanically mixed layer on the tribological characteristics of Al-Zn-Mg alloy matrix composites. The microstructure, material transfer behavior, tribological characteristics, and wear mechanism of the worn surfaces were examined. A microstructural study revealed that the reinforcements would encourage grain refining, resulting in a 60.7% average size reduction. The wear rates have significantly reduced by 50.2% and 67.2%, respectively, with the introduction of 2.0 wt% of reinforcement and T6 treatment. There is a decreasing trend of wear rate as the weight percentage of reinforcement is increased, both in as-cast and peak-aged conditions. The refractory nature of precipitates formed during T6 treatment improves the hardness of the composite and thereby reduced the wear rate. Mechanically mixed layer (MML) is observed in the worn-out surface of peak-aged composites as revealed by the SEM analysis. Overall, the Al-Zn-Mg 6 wt. % grey cast iron composite showed excellent performance in tribological characteristics.